Efficacy of curcuminoids in alleviation of iron overload and lipid peroxidation in thalassemic mice - C. Thephinlap (2018)
Non-transferrin bound iron (NTBI) is detectable in plasma of β-thalassemia patients and participates in free-radical formation and oxidative tissue damage. Desferrioxamine (DFO), deferiprone (DFP) and deferasirox (DFX) are iron chelators used for treatment of iron overload; however they may cause adverse effects. Curcuminoids (CUR) exhibits many pharmacological activities and presents β-diketone group to bind metal ions. Iron-chelating capacity of CUR was investigated in thalassemic mice. The mice (C57BL/6 stain); wild type (muβ+/+) and heterozygous β-knockout (muβth-3/+) were fed with ferrocene-supplemented diet for 2 months, and coincidently intervened with CUR (200 mg/kg/day) and DFP (50 mg/kg/day). Plasma NTBI was quantified using NTA chelation/HPLC method, and MDA concentration was analyzed by TBARS-based HPLC. Hepatic iron content (HIC) and total glutathione concentration were measured colorimetrically. Tissue iron accumulation was determined by Perl's staining. Ferrocene-supplemented diet induced occurrence of NTBI in plasma of thalassemic mice as well as markedly increased iron deposition in spleen and liver. Treatment with CUR and DFP decreased levels of the NTBI and MDA effectively. Hepatic MDA and nonheme iron content was also decreased in liver of the treated mice whilst total glutathione levels were increased. Importantly, the CUR and DFP reduced liver weight index and iron accumulation. Clearly, CUR is effective in chelation of plasma NTBI in iron-loaded thalassemic mice. Consequently, it can alleviate iron toxicity and harmfulness of free radicals. In prospective, efficacy of curcumin in removal of labile iron pool (LIP) in hepatocytes and cardiomyocytes are essential for investigation. © 2009 Bentham Science Publishers Ltd.